Dampak Etika Kerja Islam Pada Kinerja Pegawai (Studi Pada Kantor Kementerian Agama Kabupaten Hulu Sungai Utara Di Kalimantan Selatan) - Purnama Sari, Noor; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2020)
This research is a qualitative study that aims to find out how the impact of islamic work ethics on the performance of ministry of religion office employees Hulu Sungai Utara districts in south borneo. The research method uses descriptive qualitative research type with variable x, namely islamic work ethics and variable y, namely the performance of ministry of religion employees. Data collection techniques using observation, interviews and documentation. The results of the study stated that the office of the Ministry of Religion had implemented an islamic work ethic system. However, there are still some values of islamic work ethics that are lacking and must be improved. So that it has an impact on employee performance is less than the maximum. The islamic work ethic itself is very important to be implemented by the Ministry of Religion so that employee performance can be better, developed, and advanced in accordance with the targets to be achieved..